ANALISIS SEMANTIK PADA LAGU PENYANGKALAN OLEH FOR REVENGE: ARTIKEL KONSEPTUAL - Sinta Sianipar; Anggun Saputri; Maria Evelyntina Siregar; Sari Rahmdani; Inayah Hanum; Anggia Putri (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The song Penyangkalan is a For Revenge song that carries the Alternative, hardcore and rock genres. This song tells the story of someone who denies being in a toxic relationship, struggling to deal with trauma, pain and the inability to face reality. With a semantic approach, this article aims to outline how the elements in the song